2015
DOI: 10.1002/psc.2838
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory and anti‐endotoxin properties of peptides derived from the carboxy‐terminal region of a defensin from the tick Ornithodoros savignyi

Abstract: Antimicrobial peptides (AMPs) are small, cationic peptides that possess a large spectrum of bioactivities, including antimicrobial, anti-inflammatory and antioxidant activities. Several AMPs are known to inhibit lipopolysaccharide (LPS)-induced inflammation in vitro and to protect animals from sepsis. In this study the cellular anti-inflammatory and anti-endotoxin activities of Os and Os-C, peptides derived from the carboxy-terminal of a tick defensin (OsDef2), were investigated. Both Os and Os-C were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…Significantly, the hBD3-3 peptide downregulates NF-κB-dependent inflammation and, in a lung inflammation model, reduces interstitial infiltration of polymorphonuclear leukocytes. Os and Os-C are peptides derived also from the carboxy-terminal region, this time of a tick defensin [59]. Both peptides bind E. coli LPS and inhibit LPS/IFN-γ-induced NO and TNF production in murine macrophages identical to those used in the previous paragraph.…”
Section: Pro-and Anti-inflammatory Activitiesmentioning
confidence: 96%
“…Significantly, the hBD3-3 peptide downregulates NF-κB-dependent inflammation and, in a lung inflammation model, reduces interstitial infiltration of polymorphonuclear leukocytes. Os and Os-C are peptides derived also from the carboxy-terminal region, this time of a tick defensin [59]. Both peptides bind E. coli LPS and inhibit LPS/IFN-γ-induced NO and TNF production in murine macrophages identical to those used in the previous paragraph.…”
Section: Pro-and Anti-inflammatory Activitiesmentioning
confidence: 96%
“…[10,11] Bioactive peptides are commonly specific fragments of proteins that elicit biological activity and consequently modulate the health status of individuals. Some of the reported bioactivities elicited by bioactive peptides include antibacterial, [13][14][15] antifungal, [16] anti-inflammatory, [17,18] antioxidant, and angiotensin-converting enzyme (ACE) inhibitory activities. This is evident by the propensity of databases and repositories containing huge amount of data on bioactive peptide structure, properties, and activities.…”
Section: Introductionmentioning
confidence: 99%
“…At 100 μM Os PMN viability was reduced, but the effect was not statistically significant; however, evaluation of the ultrastructure of these cells showed extensive cellular damage. Malan et al found no toxicity of Os to mouse macrophages (RAW 264.7); however, lower concentrations were used in that study. There may also be differences in toxicity between mouse and human cells as well as cell lines and ex vivo cell populations.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies indicated that neither synthetic peptide, Os nor Os‐C, were toxic to erythrocytes, fibroblast, epithelial, or macrophage cell lines and possess antioxidant and anti‐inflammatory activity . Phagocytic leukocytes, neutrophils, eosinophils, and basophils play important roles in the innate immune response to pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation